2022
DOI: 10.1186/s12903-022-02444-3
|View full text |Cite
|
Sign up to set email alerts
|

What is the Oral Health-related Quality of Life following Miniscrew-Assisted Rapid Palatal Expansion (MARPE)? A prospective clinical cohort study

Abstract: Background Miniscrew-Assisted Rapid Palatal Expansion (MARPE) is a non-surgical orthodontic treatment for transverse maxillary deficiency. This study aimed to investigate the Oral Health-related Quality of Life (OHRQoL) and pain perception of patients undergoing MARPE treatment. Methods 42 consecutive patients (9 men, 33 women) from the age of 16 onwards (mean: 27.4 ± 9.3 years; range 17.1–55.7 years) who received a MARPE treatment were included. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The first-generation aligner systems have introduced hybrid systems (elastics, mini-screws, corticotomies, etc.) to support complex movements scarcely achievable with a pure system [ 9 , 10 , 13 , 16 , 17 , 18 , 19 , 20 , 21 ], but little is known about other systems in both pure and hybrid forms [ 6 , 11 , 12 , 36 ]. Thus, the attempt to find data relating to MMSC through the reciprocal movement of mesialization of other molars present and the distalization of latero-posterior teeth, brings out an important fact: this movement has not yet been described with any CA system [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first-generation aligner systems have introduced hybrid systems (elastics, mini-screws, corticotomies, etc.) to support complex movements scarcely achievable with a pure system [ 9 , 10 , 13 , 16 , 17 , 18 , 19 , 20 , 21 ], but little is known about other systems in both pure and hybrid forms [ 6 , 11 , 12 , 36 ]. Thus, the attempt to find data relating to MMSC through the reciprocal movement of mesialization of other molars present and the distalization of latero-posterior teeth, brings out an important fact: this movement has not yet been described with any CA system [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both approaches, mini-screws and corticotomies, although considered safe, are not always easily accepted by patients. They are often perceived as invasive methods, as opposed to the comfortable protocols expected from therapies with CAs [ 20 , 21 , 22 , 23 ]. The experiences reported in the literature on complex cases treated with hybrid therapies for extraction-space closures refer exclusively to traditional systematics proposed by the trademark founder of CAs (Invisalign ® , Align Technology, Inc., Tempe, AZ, USA).…”
Section: Introductionmentioning
confidence: 99%
“…Statistical power was calculated using the G*Power 3.1.9 program [ 38 , 39 ] for hierarchical multiple linear regression [ 40 ]. For this study, a total of 175 subjects was found to reach a statistical power of 0.80 and effect size of 0.35 [ 40 ] for 3 independent variables in step 1 analysis, and 4 independent variables in step 2 analysis, with a significance level (α) of 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…MARPE appliances, such as the maxillary skeletal expander (MSE) or the Dutch Maxillary Expansion Device (D-MED), are tooth-bone-borne hybrid expanders using miniscrews to transmit the forces of the expansion screw into the palate in order to overcome the resistance of the midpalatal and circummaxillary sutures [ 10 , 11 ]. MARPE was reported to be an effective and well-tolerated treatment in patients from the age of 16 onwards, with limited dental and periodontal side effects and a relatively short treatment duration [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%